SOSIALISASI STRATEGI BRANDING PRODUK DAN MANAJEMEN PEMASARAN BAGI SISWA SMK NURUL HUDA BAROS GUNA MENINGKATKAN DAYA SAING USAHA - Mesakh, Mesakh; Susanto, Denies; Ayatullah, Ayi (STAI Darul Qalam Tangerang, 2025)
This Community Service Program (PKM) aims to provide students of SMK Nurul Huda Baros with practical knowledge and skills in product branding strategies and marketing management to enhance business competitiveness. In an increasingly competitive business environment, understanding the importance of brand image and effective marketing techniques is essential for business success, especially for beginner entrepreneurs. The method applied in this program includes interactive socialization through material presentations, discussions, case studies, and branding simulations. The results indicate an improvement in students' understanding of branding elements, market segmentation, and digital marketing strategies. This program is expected to foster students’ entrepreneurial spirit and improve the quality and competitiveness of the products they create.